Strategy of Islamic Religious Instructors in Religious Development of the Da'wah Village Community at Punggur District - Susilowati, Indah; Mukmin, Hasan; Rosidi, Rosidi; Nopryana, Rahmah Dwi (Bulletin of Science Education, 2023)
Islamic religious counselors generally engage in oral preaching. However, the needs of the community are not limited to intellectual and spiritual aspects alone, thus requiring a developmental strategy in the form of actions or initiatives. This research discusses the strategies employed by Islamic religious counselors in empowering the community of Kampung Dakwah in the Punggur District of Central Lampung Regency. The study aims to analyze the strategies of Islamic religious counselors, identify challenges, and examine the outcomes achieved through the implementation of the strategies used by Islamic religious counselors in empowering the community in Kampung Dakwah. This research is qualitative in nature and employs observation, interviews, and documentation as methods of data collection. The data sources are divided into two categories: primary data sources and secondary data sources, which will be analyzed using data triangulation and conclusion drawing methods. The findings of this research indicate that: (1) The strategies employed by Islamic Religious Counselors in community empowerment in Kampung Dakwah are carried out through stages of awareness raising, transformation of intellectual improvement, and strategy evaluation. (2) The challenges faced include the limited capability of religious counselors in the field of economic empowerment. (3) The outcomes achieved include the reduction of social issues, improved economic conditions for productive-aged poor families, and a decrease in illiteracy rates in reading the Quran in Kampung Dakwah. Keywords: Strategy of Islamic Religious Instructors. Religious Counselor, Community Development